Using the photoplethysmography method to monitor age-related changes in the cardiovascular system - Djurić, Biljana; Žikić, Katarina; Nestorović, Zorica; Lepojević-Stefanović, Danijela; Milošević, Nebojša; Žikić, Dejan (Frontiers in Physiology, 2023)
Introduction Aging is a physiological process characterized by progressive changes in all organ systems. In the last few decades, the elderly population has been growing, so the scientific community is focusing on the investigation of the aging process, all in order to improve the quality of life in elderly. One of the biggest challenges in studying the impact of the aging on the human body represents the monitoring of the changes that inevitably occur in arterial blood vessels. Therefore, the medical community has invested a great deal of effort in studying and discovering new methods and tools that could be used to monitor the changes in arterial blood vessels caused by the aging process. The goal of our research was to develop a new diagnostic method using a photoplethysmographic sensor and to examine the impact of the aging process on the cardiovascular system in adults. Long-term recorded arterial blood flow waveforms were analyzed using detrended fluctuation analysis. Materials and Methods The study included 117 respondents, aged 20 to 70 years. The arterial blood flow waveform was recorded for five minutes, with an optical sensor placed above the left common carotid artery, simultaneously with a single-channel ECG. For each cardiac cycle, the blood flow amplitude was determined, and a new time series was formed, which was analyzed non-linearly (DFA method). The values of the scalar coefficients α1 and α2, particularly their ratio (a1/a2) were obtained, which were then monitored in relation to the age of the subjects. Results The values of the scalar ratio (α1/α2) were significantly different between the subjects older and younger than 50 years. The value of the α1/α2 decreased exponentially with the aging. In the population of middle-aged adults, this ratio had a value around 1, in young adults the value was exclusively higher than 1 and in older adults the value was exclusively lower than 1. Conclusions The results of this study indicated that the aging led to a decrease in the α1/α2 in the population of healthy subjects. With this non-invasive method, changes in the cardiovascular system due to aging can be detected and monitored.